Intraoperatively Detected But Previously Indocyanine Green–Negative Lymphatic Vessels May Have Misprized Potentials and Should Not Be Neglected in Lymphaticovenous Bypass Surgery. Issue 1 (July 2019) - Scaglioni, Mario F.; Uyulmaz, Semra; Arvanitakis, Michael; Lineaweaver, William C.; Zhang, Feng
Abstract : Introduction: Identification of patent lymphatic vessels without fibrosis and with high flow is difficult but crucial in the preoperative planning of lymphaticovenous anastomosis (LVA). Lymphatic vessels on the operating field cannot always be visualized preoperatively because of the anatomical and physiological characteristics of lymphedema tissue. The purposes of this study were to demonstrate our clinical experience in identifying indocyanine green (ICG)–negative lymphatics intraoperatively and to emphasize the therapeutic potential of performing anastomoses with ICG-negative lymphatics. Methods: Indocyanine green–positive lymphatic ducts were marked preoperatively in 5 patients with lower extremity lymphedema; moreover, if ICG-negative lymphatics were identified during surgery, they were used for additional LVA thus implementing multiple anastomoses in one surgical setting. Results: In total, 33 LVAs were performed in 5 patients with lower extremity lymphedema, of which 11 LVAs were implemented with ICG-negative lymphatics. Immediately after the anastomosis, a strong lymphatic drainage could be appreciated in all cases. Six months postoperatively patients reported a subjective decrease in limb circumference and pressure sensation. Conclusions: We believe that ICG-negative lymphatics found intraoperatively should be evaluated for additional LVAs in order to maximize drainage effect and might provide better outcomes.